Determinants of using online shopping in European Union countries - Huterska, Agnieszka; Huterski, Robert (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Online shopping has gained increased economic importance as a result of restrictions on brick-and-mortar purchases due to the COVID-19 pandemic. Notwithstanding the natural partial return of consumers to direct purchases with the lifting of restrictions by the authorities, interest in online shopping does not return to pre-pandemic levels. Aim: The aim of the article is to verify the influence of various factors on the propensity to use online shopping in the European Union countries in the period 2010–2021. Due to the temporal and geographical scope of data, the panel method was used in the research. Results: The research on the determinants of online shopping, carried out by the authors, showed the statistical significance of all eight dependent variables affecting the share of people who shop online in the societies of the European Union countries. The increase in the use of online shopping is influenced by both the quality of Internet connections, the general frequency of Internet use, readiness to search the Internet for information about goods and services and the use of Internet banking. This regularity also occurs in the case of the share of older people in society, the share of people with at least the second level of education, the share of people employed in science and technology, and the level of GDP per capita.